HYPERTRIGLYCERIDEMIC WAIST AND ASSOCIATED FACTORS IN CHILDREN AND ADOLESCENTS WITH TYPE 1 DIABETES MELLITUS - Lílian Caroline de Souza e Silva; Skalyt Lee Barbosa e Silva; Ávilla Monalisa Silva de Oliveira; Jacqueline Rosangela de Araujo; Ilma Kruze Grande de Arruda; Regiane Maio; Maria da Conceição Chaves de Lemos (Sociedade de Pediatria de São Paulo, 2020)
ABSTRACT Objective: To assess the frequency of the hypertriglyceridemic waist phenotype and its associated factors in children and adolescents with type 1 diabetes mellitus. Methods: This is an observational analytical study with individuals with type 1 diabetes mellitus, aged 5 to 18 years, of both genders, followed in a university hospital in the Brazilian Northeast. Weight, height, and waist circumference were measured, and the lipid profile and glycated hemoglobin were analyzed. The hypertriglyceridemic waist phenotype was defined by the simultaneous presence of increased waist circumference (≥90th percentile for age and gender) and elevated serum triglyceride levels (≥75 mg/dL for children and ≥90 mg/dL for adolescents). We also investigated the family history of cardiovascular diseases and diabetes, as well as sociodemographic and behavioral variables. In the statistical inference tests, the proportions were compared by Pearson's chi-square test and/or Fisher's exact test, being significant p<0.05. Results: A total of 102 patients were evaluated, most of them females (54.9%) and adolescents (66.7%). The frequency of hypertriglyceridemic waist was 23.5%, which was associated with females (p=0.043), overweight (p=0.023), hypercholesterolemia (p=0.002), high LDL (p=0.001), and borderline VLDL (<0.001). Conclusions: The frequency of the hypertriglyceridemic waist phenotype was associated with females, atherogenic lipid profile, and overweight, indicating the importance of the nutritional monitoring of this population, aiming at reducing future cardiovascular diseases.